Pelatihan Mikrokontroler Dalam Pengenalan Robotika Sebagai Respon Revolusi Industri 4.0 Di SMK Media Informatika Dasana Indah Tengerang - Meyhart Bangkit Sitorus; Albert Gifson; Juara Mangapul; Hastuti Aziz (Terang, 2020)
Industry 4.0 fundamentals involve at least 4 thing : interconnection (machines, devices and people are connected), information transparency (data analysis needs), decentralized decisions (effects of interconnection and information transparency) and technical assistance (the purpose of industry 4.0). Collaboration between machines / devices and humans is very important to implement Industry 4.0. In this collaboration, the role of the microcontroller as a connector between machines and humans. Microcontroller Training for Introduction of Robotics as a Response to the Revolution of Industry 4.0 at SMK Media Informatika Dasana Indah Tengerang is aimed for students and teacher so they know about Industry 4.0 and its application in microcontroller programming. Therefore the method of PKM program consists of seminar and workshop. The seminar explained about Industry 4.0 Revolution and the workshop is programming Line Follower which is embedded with Arduino Uno. Result of this PKM program in the form of industry 4.0 revolution seminar combine with microcontroller programming workshop, this combination give bigger impact compared with just given a seminar or just a workshop. The students and teacher who attend this event get additional knowledge about Industry 4.0 and how to program a microcontroller.